Cost of capital (Henry Stewart Talks, 2026)
Introduction to Cost of Capital, Importance in Corporate Finance, Components of Cost of Capital, Weighted Average Cost of Capital, Cost of Capital as Hurdle Rate, Quantitative Methods Using Cost of Capital, Adjusting Cost of Capital for Risk, Use of Big Data in Estimating Cost, Impact on Firm Valuation and Advantage